(untitled) (Research, Society and Development, 2020)
The chemical, physical and biological conditions of the soil are extremely important to obtain satisfactory agricultural production. The no-tillage system (SPD) contributes to minimize soil loss in the crop, ensuring the stability of its aggregates by minimal soil tillage and overlapping the soil with a vegetable layer. The present work aims, through a review of available literature, to show that the no-tillage system promotes soil restructuring through the action of organic matter built by crop residues from the crop rotation process. Aiming to minimize problems in agricultural production as the beginning of the erosive process, the SPD uses conservation techniques to promote soil decompression and increase the biodiversity of the production system through the diversity of species provided by the crop rotation and succession process. Thus, the no-tillage system increases the natural fertility of the soil by decomposing organic matter and intercropping with leguminous plants that increase the concentration of nitrogen (N) in the soil. Thus, it can be concluded that SPD provides numerous short, medium and long term benefits, enabling the solution of environmental problems found in the area of agricultural production, making the system more sustainable. In this work a bibliographical revision about the theme is made.